Polymeric Scaffolds in Tissue Engineering Application: A Review - Brahatheeswaran Dhandayuthapani; Yasuhiko Yoshida; Toru Maekawa; D. Sakthi Kumar (International Journal of Polymer Science)
Current strategies of regenerative medicine are focused on the restoration of pathologically altered tissue architectures by transplantation of cells in combination with supportive scaffolds and biomolecules. In recent years, considerable interest has been given to biologically active scaffolds which are based on similar analogs of the extracellular matrix that have induced synthesis of tissues and organs. To restore function or regenerate tissue, a scaffold is necessary that will act as a temporary matrix for cell proliferation and extracellular matrix deposition, with subsequent ingrowth until the tissues are totally restored or regenerated. Scaffolds have been used for tissue engineering such as bone, cartilage, ligament, skin, vascular tissues, neural tissues, and skeletal muscle and as vehicle for the controlled delivery of drugs, proteins, and DNA. Various technologies come together to construct porous scaffolds to regenerate the tissues/organs and also for controlled and targeted release of bioactive agents in tissue engineering applications. In this paper, an overview of the different types of scaffolds with their material properties is discussed. The fabrication technologies for tissue engineering scaffolds, including the basic and conventional techniques to the more recent ones, are tabulated.